PECULIARITIES OF VISUAL MAPPING OF SPORTS LIFE IN STREET ART OF UKRAINE - Кузнецова, І. О.; Лільчицький, О. В. (Art and Design, 2020)
Determining the features of the visual display of sports life in the existing street art of Ukraine. Issuing recommendations on the conceptual improvement of the visual display of sports life in the existing street art of Ukraine, for the created objects of art and design related to the reflection of personality in sports. The paper used the methods of systematization and updating of analytical information about the features of the visual display of sports topics in the street art of Ukraine. The accumulation, systematization and implementation of information was carried out by studying specialized professional literature, relevant sites, field studies in Kyiv and the region. Studies were conducted with a focus on street art in large cities of Ukraine. The main displays of sports life in the existing street art of Ukraine are identified and characterized. The main trends of the visual series of modern street art of Ukraine, reflecting sporting events, are described. A comparative analysis of some trends in the design of murals and graffiti is done. Abstract recommendations are given for improving street art in the country. The paper describes the features of street sculpture, murals and graffiti of the country. Abstract recommendations are given to improve the modern street art of Ukraine, aimed to solve aesthetic and, as a result, ethical problems.The paper shows modern trends in the design of murals and graffiti of Ukraine, reflecting the sports life of Ukraine, which can serve as a guide for creating new murals.